A Study on the Impact of IoT Technologies on Enhancing Smart Home Automation at Cognifyz Technologies, Nagpur - Manghate, Shailesh Ramesh; Rewatkar, Abhay (Journal of Neonatal Surgery, 2025)
The integration of Internet of Things (IoT) technologies in smart home automation has gained significant momentum, transforming the way residential spaces are managed. IoT-enabled devices provide seamless connectivity, enabling users to monitor and control various aspects of their homes, such as security, lighting, temperature, and appliances, via smartphones or other internet-connected devices. At Cognifyz Technologies in Nagpur, the implementation of IoT solutions in smart home systems aims to enhance the user experience by improving efficiency, convenience, and energy management. This study delves into the impact of IoT technologies on smart home automation, focusing on their role in optimizing home management and providing tailored, user-friendly solutions. By examining the benefits, challenges, and future potential of IoT in smart homes, the research explores how these technologies influence consumer behaviour and shape the future of residential living. The findings indicate that IoT-based smart homes lead to increased automation, better energy efficiency, and heightened security. However, issues such as connectivity, data privacy concerns, and high initial costs need to be addressed to unlock the full potential of IoT in residential spaces. The study concludes that as IoT technologies evolve, they will continue to reshape the smart home landscape, contributing to the creation of more sustainable and intelligent living environments